Design and development of self-healing dental composites. (15th March 2016) - Huyang, George; Debertin, Anne E.; Sun, Jirun
Abstract: The purpose of this project is to design and develop a clinically applicable self-healing dental composite (SHDC). The value of resin-based dental restorations could be improved by increasing their service lives. One way to improve longevity is to obturate micro-cracks that form during or after the composite hardens in the dental cavity. Toward this end, we introduce here a new type of SHDC made with contemporary dental components plus two additional ingredients: a healing powder (HP, strontium fluoroaluminosilicate particles) and a healing liquid (HL, aqueous solutions of polyacrylic acids) that is enclosed within silica microcapsules. As micro-cracks develop, they will break the microcapsules in their propagation path, thereby releasing HL. This liquid will then react with particles of HP exposed by the crack formation, forming an insoluble reaction product that fills and seals the cracks. The key factors to achieve these self-healing of cracks are discussed. The elastic modulus of a SHDC appeared to be satisfactory. The healing process was confirmed by means of mechanical, morphological, and chemical methods. The SHDC restored micro-cracks without external intervention, thereby showing potential for increasing the service lives of dental restorations. Importantly, this SHDC contains only clinically-tested, biocompatible materials, making it readily applicable. Graphical abstract: Highlights: A self-healing dental resin composite (SHDC) is designed and developed. The SHDC can respond and heal micro-cracks autonomously. A clinically applicable chemistry is used to achieve self-healing.